Gender-based violence among women and girls in conflict-affected areas of Northeast Amhara, Ethiopia - Dellie, Endalkachew; Salelew, Endalamaw; Mihret Fetene, Samrawit; Negash, Wubshet D.; Kebede, Adane; Haile, Tsegaye G.; Alemu, Melaku Birhanu; Park, Jinha; Tefera, Selamawit; Alene, Bruhtesfa Mouhabew; Atnafu, Asmamaw (Frontiers in Global Women's Health, 2024)
BackgroundGender-Based Violence (GBV) is one of the major problems that women and girls encountered during the conflict between the Ethiopian federal government and the Tigray People's Liberation Front (TPLF). However, there is a gap in evidence regarding gender-based violence resulting from the ongoing conflict in these areas. Therefore, this study assessed the prevalence of GBV and its contributing factors in the conflict-affected northeastern Amhara region of Ethiopia.MethodsA community-based cross-sectional study was conducted from July 7th to September 30th, 2023, among 597 women and girls who lived in the three most conflict-affected districts (Wadla, Lay-Gaynt, and Meket) in northeastern Amhara regional state of Ethiopia. GBV was assessed using the WHO multi-country study on women's health and domestic violence against women questionnaire, which has 13 items and measures three violence domains (emotional, physical, and sexual). A binary logistic regression analysis was conducted. We used Adjusted Odds Ratios (AOR) with their respective 95% Confidence Intervals (CI) and a p-value of <0.05 to identify statistically significant factors.ResultsThe overall prevalence of gender-based violence was 39.0% (95%CI: 35.2–43.6); 36.7% were experienced emotional, 15.4% physical, and 8.9% sexual violences. The burden is higher among individuals who are divorced, substance users, have low social support, or have participated in the war.ConclusionsTwo-fifths of women and girls in conflict-affected areas of the northeastern Amhara region experienced violence. Thus, collaboration between healthcare providers and policymakers is needed to enhance care for victims, including the provision of social support and substance use mitigation.